Ligation of the Intersphincteric Fistula Tract (LIFT): A Minimally Invasive Procedure for Complex Anal Fistula: Two-Year Results of a Prospective Multicentric Study. (October 2014) - Sileri, Pierpaolo; Giarratano, Gabriella; Franceschilli, Luana; Limura, Elsa; Perrone, Federico; Stazi, Alessandro; Toscana, Claudio; Gaspari, Achille Lucio
Introduction . The surgical management of anal fistulas is still a matter of discussion and no clear recommendations exist. The present study analyses the results of the ligation of the intersphincteric fistula tract (LIFT) technique in treating complex anal fistulas, in particular healing, fecal continence, and recurrence. Methods . Between October 2010 and February 2012, a total of 26 consecutive patients underwent LIFT. All patients had a primary complex anal fistula and preoperatively all underwent clinical examination, proctoscopy, transanal ultrasonography/magnetic resonance imaging, and were treated with the LIFT procedure. For the purpose of this study, fistulas were classified as complex if any of the following conditions were present: tract crossing more than 30% of the external sphincter, anterior fistula in a woman, recurrent fistula, or preexisting incontinence. Patient's postoperative complications, healing time, recurrence rate, and postoperative continence were recorded during follow-up. Results . The minimum follow-up was 16 months. Five patients required delayed LIFT after previous seton. There were no surgical complications. Primary healing was achieved in 19 patients (73%). Seven patients (27%) had recurrence presenting between 4 and 8 weeks postoperatively and required further surgical treatment. Two of them (29%) had previous insertion of a seton. No patients reported any incontinence postoperatively and we did not observe postoperative continence worsening. Conclusion . In our experience, LIFT appears easy to perform, is safe with no surgical complication, has no risk of incontinence, and has a low recurrence rate. These results suggest that LIFT as a minimally invasive technique should be routinely considered for patients affected by complex anal fistula.